Extraction of surface wind and current patterns from sar imagery - Maiyas, Mohamed; Marghany, Maged; Mansor, Shattri; Khuzaimah, Zailani (2005)
The capacity of synthetic aperture radar (SAR) to observe the sea surface and its potential for evaluating the marine studies, interpretation of atmospheric and oceanic phenomena make it a very useful tool for monitoring this study. In this paper the CMOD-4 and CMODIFR2 models are applied in the extraction Sea surface wind and current patterns from RADARSAT-1 SAR images. SAR wind field retrieval is a two-steps process. The first step is to retrieve wind directions, which is an important input to the second step to retrieve wind speeds. The SAR wind speed retrieval is dependent upon the accuracy of wind directions. Doppler shift frequency and polynomial function applied to extract the current speed and direction. The study shows poor result for CMOD-4 and good result for CMODIFR2 model. It can be concluded that CMODIFR2 model is a useful tool to extract sea surface wind and current patterns from RADARSAT-1 SAR images.